HEPATOPROTECTIVE EFFECT OF GAMAVUTON-0 AGAINST D˗GALACTOSAMINE/LIPOPOLYSACCHARIDE-INDUCED FULMINANT HEPATIC FAILURE - Arief Nurrochmad; Ika Puspita Sari; Retno Murwanti; Sardjiman .; Triana Candraningrum; Dyah Afritasari; Devina Martina; Iren Wati Siahaan (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
The objective of this study is to determine the hepatoprotective effect of GVT-0 (one of curcumin analogues) against liver damage in rat-induced D-galactosamine (D-GalN)/lipopolysaccharide (LPS) as a model of fulminant hepatitis. In the study D˗GalN/LPS elevated serum GPT activity that indicate a particular occurrence of liver damage due to depletion of UTP and UDP-glucuronic acid. Administration of GVT-0 (10 mg/kg) showed decreased enzyme activity of SGPT/SGOT but had no effect on serum ALP and total bilirubin levels, whereas at doses of 20 and 40 mg/kg, the protective effect of GVT-0 was decrease. The glutathione content in the D-GalN/LPS (0.76 ± 0.07) mol/g liver content was found lower than controls (0.90 ± 0.03) mol/g liver. Administration of GVT-0 dose of 10, 20 and 40 mg/kg restored glutathione content returned to normal levels. The results showed that treatment of GVT-0 showed no effect on TBARS and catalase activity. Treatment of D-GalN/LPS, indicating the trend of increased TNF-α, although statistically not significant, while the administration of GVT-0 showed a tendency to decrease the concentration of TNF-α. All findings of the results indicated that the GVT-0 mainly lower dose (10 mg/kg) showed hepatoprotective action in rat model of fulminant hepatitis induced by D-GalN/LPS. The results indicated that the mechanism of hepatoprotective effect of GVT-0 is not via antioxidant properties of GVT-0. However, further studies are necessary to explain the molecular mechanism of hepatoprotective effect of GVT-0.Key words: Gamavuton-0, hepatoprotective, fulminan hepatitis, D˗galactosamine/LPS